Autism spectrum disorder and de-escalation strategies : a practical guide to positive behavioural interventions for children and young people - Brown, Steve, 1970- (Jessica Kingsley Publishers, 2015)
Discussing a variety of de-escalation and behaviour management strategies, this book offers practical guidance on using non-physical and physical interventions to support children (aged 3-18) on the autism spectrum or with emotional, social and behavioural difficulties, and to keep them and others safe.